Pengaruh Terapi Relaksasi Autogenic Terhadap Tingkat Nyeri Akut Pada Pasien Abdominalpain Dengan Post Appendektomi Di Ruangan Flamboyan Rumah Sakitm TK II Robert Wolter Mongisidi Manado - Reka Puspita Djumaati; Silvia D Mayasari Riu; Zainar Kasim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Autogenic Relaxation Therapy is an exercise of one of the relaxation techniques that comes from oneself in the form of short sentences to be able to make the mind peaceful. The aim was to determine the effect of autogenic relaxation therapy on acute pain levels in abdominal pain patients with post appendectomy in the flamboyant room of Rumkti Tk II Robert Wolter Mongisidi Manado. The research method is qu a si experiment with One group pre test and post test design design with a sample of 11 respondents. The sampling technique using Total Sampling is a sampling method using SOPs and observation sheets. Furthermore, the collected data was processed using McNemar's statistical test. The results showed that most respondents experienced changes after doing Autogenic Relaxation Therapy. The results of data analysis tested using McNemar obtained results p = 0.004 (a < 0.005) meaning that there was an effect of autogenic relaxation therapy on post-appendectomy patients in the flamboyant room of Rumkit TK II Robert Wolter Mongisidi Manado. Conclusion There is an effect of autogenic relaxation therapy on acute pain levels in abdominal pain patients with post appendectomy in the flamboyant room of Robert Wolter Mongisidi Kindergarten II Hospital.